Comparative Study In Personality States And Self Confidence In Physical Educators and Educators of Different Majors - Mohsen, Noha (Journal of Physical Education, 2019)
The problem of research lies in answering the following question; does physical education as a major affect personality traits and their self confidence? The research aimed at identifying personality traits and self confidence of female physical educators as well as other majors’ educators. The researcher used the descriptive method on (46) educators 23 physical educators and 23 educators of other subjects. The data was collected and treated used proper statistical operations to conclude significant statistical differences in self confidence and personality traits among educators in favor of physical educators.